Using Taguchi method to obtain the optimal design of heat dissipation mechanism for electronic component packaging. (October 2016) - Huang, De-Shau; Tu, Wen-Bin; Zhang, Xiu-Ming; Tsai, Liang-Te; Wu, Ti-Yuan; Lin, Ming-Tzer
Abstract: Packaging technology developments in semiconductor chips are moving towards miniaturization, thinner products, lighter weights, and higher performance. However, in the process of packaging, warpage and residual stress have always been major problems, such as pin deviation, breakage, and weak signals. Further, the distinctive properties of the numerous materials that comprise a semiconductor chip demand different molding temperatures; thus, excessive internal thermal stresses are produced within the packaging structure which ultimately results in colloid warpage. This study used a 3D coordinate measuring machine to determine the levels of warpage produced in electronic packaging products and to verify the amount of warpage simulated by the finite element method. Then, Taguchi method was also utilized to analyze and discuss the four critical control factors namely: (1) shape of the heat sink; (2) thickness of molding; (3) molding temperature; and (4) thickness of soldering tin. Thus, the minimum thermal stress for electronic packaging components was obtained, which meant the optimal parameter combination for the packaging was a triangle-shaped heat sink, with a molding compound of 1.175 mm thick, a molding temperature of 170 °C, and a soldering tin that was 0.03 mm thick. Highlights: Measuring the warpage produced in electronic packaging product and simulated by the finite element method. Used Taguchi method to analyze and discuss the four critical control factors. The minimum thermal stress and the optimal parameter combination for the packaging was a triangle-shaped heat sink.